Awareness, Knowledge and Use of Online Survey Tools amongst Researchers in Nigerian Higher Institutions - F. N, Francisca Okoroma (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
There is a growing prevalence of online survey for academic research. This can be attributed to the great impact of online survey tools on the researchers’ ability to easily develop, disseminate instruments, assemble and analyze data. Though many researchers in the advanced world have become very prone to the use of online survey, their counterparts in the developing economy are still struggling in the adoption of this invaluable tool. This study examines the level of awareness, knowledge and use of online survey tools amongst academic researchers in Nigeria. Questionnaire instrument was used for data collection. The population used for the study consists of eighty academic researchers in higher institutions spread across various parts of Nigeria. The study found that although there is a high level of awareness and preference to online survey tools by Nigerian researchers, yet there is a very low level of knowledge and usage of online survey tools by Nigerian researchers. The reason being that the researchers lack the basic prerequisite skills needed for the processing and development of online survey, amongst other challenges. The study ascertained that Survey Monkey was the most popular and predominantly used survey tool by Nigerian researchers, followed by Survey PRO and Zoomrang. The study advocated for trainings and workshops on the use of the survey tools in higher institutions in Nigeria, which could be facilitated by the survey tools’ designers in collaboration with higher institutions in Nigeria.